Prospects of Using Biopolymeric Films in Medicine and Pharmacy - Khokhlenkova, N. V. (Asian Journal of Pharmaceutics (AJP), 2018)
Introduction: Nowadays, biopolymers and biomaterials are an actively developing field, interesting both for specialists from various fields of science and for society at large. The range of polymers of both natural and synthetic origin is constantly expanding, but only a few of them are used in pharmaceutical production and medical practice. Due to the composition of polymers and active pharmaceutical ingredient, films are a promising form for applying in dentistry, ophthalmology, surgery, and other fields of medicine. Materials and Methods: In the work marketing and economic research methods are used to ground social and medical practicability of developing new dental products for local treatment. Results and Discussions: Based on the data of modern scientific literature, the requirements for medicinal films are outlined, their classification is given. Approaches to the choice of active and auxiliary substances in the process of developing new film formulations are described. The prospects of using films in surgery, dentistry, ophthalmology, and dermatology are shown. Conclusions: Based on the review, polymer films have been classified, and the requirements for the given dosage form have been defined. Approaches to selecting active and auxiliary ingredients have been considered. The main aspects of the technological process for the preparation of films are described. The ways of rational application of films in medical practice have been highlighted.